Security and safety in Los Angeles high-rise buildings after 9/11 - Archibald, Rae W. (Documented briefing (Rand Corporation), 2002)
In the wake of September 11 this text identifies generic terrorism threats to, and practices used to safeguard, high-rise buildings in Los Angeles and elsewhere. It discusses potential responses after an event and suggests preparations that local government and the private sector could take.